Application of Rasch Model for Validating Creative Thinking Test on Solar Cell Material - Septiyanto, Arifin; Prima, Eka Cahya; Rusyati, Lilit; Lutianasari, Lia; Setiawan, Andhy (UIN Fatmawati Sukarno Bengkulu, 2024)
Creativity is regarded as essential for work, thinking, and life in the twenty-first century. Teaching solar cells can influence and encourage students' creative thinking skills. This research aims to evaluate the creative thinking skills of Indonesian students, validate the innovative thinking skills test adapted for Indonesia, and classify the difficulty level of the questions and students' creative thinking skills. The participants were 32 students from 10th-grade high school at a college in Bandung, West Java, Indonesia. The creative thinking skills test consists of essay questions. Data collection was carried out through paper-based tests. The results of the Rasch analysis show that the adapted creative thinking skills test meets the validity and reliability criteria based on Rasch parameters. Differential item function (DIF) analysis shows that only two of the 12 items fall into the bias question category, so they need to be reviewed. The study's implication can help teachers and researchers anticipate student success rates in disciplines other than mathematics and science. This is because creative thinking skills must be included in the Merdeka curriculum